﻿The relationship between statin therapy and adipocytokine/inflammatory mediators in dyslipidemic nondiabetic patients: A comparative study - Hany A. Al-hussaniy; Ahmed Hamza Al-Shammari; Hayder Naji Sameer; Amjad I. Oraibi (Pensoft Publishers, 2023)
Background: Statins have emerged as a vital therapeutic option for dyslipidemia, effectively reducing morbidity and mortality in individuals with various medical conditions. Recent research has shed light on the intricate pathophysiology of atherosclerosis, which involves lipid accumulation and inflammatory mediators. This research was conducted to assess the correlation between statin therapy and adipocytokine and inflammatory mediator levels in dyslipidemic nondiabetic patients. Methods: A total of 67 dyslipidemic nondiabetic patients were enrolled, alongside 33 healthy controls. The participants were categorized into three groups: Group (A), comprising patients undergoing statin therapy (n = 34), Group (B), consisting of patients not receiving statin therapy (n = 33); and Group (C), comprising healthy controls (n = 33). Results: Patients not receiving statin therapy exhibited significant dyslipidemic profiles compared to patients undergoing statin therapy and healthy controls. Levels of total cholesterol (TC), triglycerides (TG), very low-density lipoprotein (VLDL), and low-density lipoprotein (LDL) were higher in patients not receiving statin therapy. Serum levels of proprotein convertase subtilisin/kexin type 9 (PCSK9) were higher in the statin group than in the non-statin group and controls. Additionally, PCSK9 levels were higher in patients treated with rosuvastatin than those treated with atorvastatin. Conversely, levels of retinol-binding protein 4 (RBP4) were lower in the statin group compared to the non-statin group and controls. Although no significant difference in RBP4 levels between atorvastatin and rosuvastatin users was found, atorvastatin displayed lower RBP4 values. The study also revealed lower C-reactive protein (CRP) levels in the statin group, primarily in the rosuvastatin subgroup, compared to the non-statin group. Conclusion: Statin therapy increased PCSK9 levels, with a more pronounced rise observed in patients treated with rosuvastatin than atorvastatin. Statin therapy proved protective by reducing RBP4 and CRP levels in dyslipidemic nondiabetic patients.